A method for preparing spherical alumina

By introducing a crosslinked structure in the preparation process of spherical alumina, forming a network structure and calculating at high temperature, the problems of pore structures prone to collapse and difficulty in controlling dopants in the prior art are solved, and the preparation of spherical alumina with high strength, large pore volume and stability is achieved.

CN119774644APending Publication Date: 2025-04-08CHINA CATALYST HLDG CO LTD

Patent Information

Application Number
CN202411985857.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the existing spherical alumina preparation process, after the pore reamer adjusts the large pore structure, the pore structure is prone to collapse, the product stability is poor, the strength is low, and dopants such as zirconium, titanium, and silicon are required to add dopants such as zirconium, titanium, and silicon. It is difficult to precisely control and affect performance.

Method used

By introducing a crosslinked structure into the aluminum sol, a network structure is formed, and a connected pore is formed after high temperature calcination, the use of pore reamers and the introduction of impurities are avoided, and the pore structure and strength are optimized.

Benefits of technology

The high strength and large pore volume of spherical alumina are optimized, the pore structure is stable, the influence of impurities is avoided, the preparation process is simplified, and it is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for preparing spherical alumina, and relates to the technical field of spherical alumina. The preparation method of the present invention comprises the following steps: mixing pseudo-boehmite powder with water to obtain a suspension, then adding a peptizing agent for peptization to obtain an aluminum sol; adding a cross-linking substrate and a cross-linking agent to the aluminum sol to obtain a sol containing a prepolymer, and then adding a coagulant to obtain a mixed sol; dripping the mixed sol into a hot oil column for molding, and obtaining spherical alumina after aging, washing, drying, and roasting. The present invention adopts a hot oil column molding method, which does not require the addition of a pore expanding agent or new equipment, and the preparation process is simple and does not introduce new impurities, so it is suitable for industrial production. The pore volume of the spherical alumina prepared by the present invention reaches 0.60cm 3 / g or more, and can be used as a propane dehydrogenation catalyst carrier.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of spherical alumina, and in particular to a preparation method of spherical alumina. Background Art

[0002] Alumina has a high specific surface area, good chemical stability and thermal stability, and excellent mechanical strength. Its crystal phase and pore structure are diverse, suitable for a variety of catalytic reactions, and has been widely used in many fields such as petrochemicals, environmental protection, and automobile exhaust treatment. For example, in the field of petrochemicals, alumina carriers are used to prepare hydrogenation catalysts, cracking catalysts, etc.; in the field of environmental protection, it is used to prepare VOCs treatment catalysts; in the field of automobile exhaust treatment, it is used to prepare three-way catalysts, etc. In addition, the regeneration rate and safety of alumina catalysts are high, which is conducive to industrial applications. In industrial applications, spherical alumina has good particle fluidity, which is conducive to uniform distribution and mixing during the processing process. Its spherical structure reduces wear during mixing and processing, and extends the life of the equipment. It is currently the most widely used shaped alumina.

[0003] The methods for preparing spherical alumina carriers include rolling ball forming method, hot oil column forming method, oil-ammonia column ball forming method, and spray dispersion ball forming method. Among them, the products prepared by the hot oil column forming method have high strength, regular and uniform shape, and its forming operation is simple and efficient. It is one of the important methods for preparing high-quality spherical alumina in industry. The general process of the hot oil column forming method is: the aluminum sol is gelled under given conditions to form small balls with a fixed shape; then the gel small balls are subjected to a precipitation process under a certain temperature and pressure to convert them into hydrated alumina; finally, the chemically bound water is removed and the crystal form is changed during the roasting process to obtain a finished spherical alumina carrier.

[0004] The invention patent with publication number CN104039705A discloses a method for manufacturing spherical alumina particles, which method includes the following steps: a) preparing a suspension comprising water, an acid and at least one boehmite powder, for which the ratio of the crystal size in the

[020] and

[120] directions obtained using the Scherrer X-ray diffraction formula is 0.7 to 1; b) adding a pore former, a surfactant and optionally water, or an emulsion comprising at least one pore former, a surfactant and water to the suspension of step a); c) mixing the suspension obtained in step b); d) using the suspension obtained in step c) to form the spherical particles by droplet solidification method; e) drying the particles obtained in step d); f) calcining the particles obtained in step e).

[0005] The invention patent with publication number CN110423135A discloses a porous alumina ceramic and a method for making the same, wherein the porous alumina ceramic is obtained by in-situ injection molding and sintering of a ceramic slurry, wherein the ceramic slurry includes a dispersant, a gelling agent, a solid-phase ceramic component and water, wherein the solid-phase ceramic component accounts for 60 to 70% of the weight of the ceramic slurry, the dispersant accounts for 0.1 to 0.8% of the weight of the solid-phase ceramic component, the gelling agent accounts for 0.2 to 1.0% of the weight of the solid-phase ceramic component, the solid-phase ceramic component includes alumina, a sintering aid and a pore-forming agent, the weight ratio of alumina to the sintering aid is 70 to 90:10 to 30, the pore-forming agent accounts for 10 to 40% of the sum of the weight of alumina and the sintering aid, and the sintering aid includes a submicron silicon compound. This method combines in-situ injection molding, special sintering aids and gelling agents to ensure that the surface of the porous alumina ceramics produced will not crack or peel, and will have a good appearance. The apparent porosity can reach 60-70%, and the bending strength is 20-30 MPa. This porous alumina ceramic can have both high porosity and high strength.

[0006] It can be seen that in the current spherical alumina preparation process, a pore expander is generally required to expand the pores and adjust the macropore structure to ensure the comprehensive performance of the spherical alumina. However, after high-temperature calcination, the pore structure of the spherical alumina is prone to collapse, the product has poor stability and low strength, and seriously affects the use effect. In addition, dopants such as zirconium, titanium, and silicon are mostly required to be added during the preparation process, and the type and amount of the dopant need to be precisely controlled, otherwise it will have a negative impact on the product performance and the application occasions are limited. Summary of the invention

[0007] In view of this, the present invention provides a method for preparing spherical alumina, which introduces a cross-linked structure to form a network structure inside the small ball, and forms interconnected pores after high-temperature calcination, thereby finally obtaining high-strength, large-pore-volume spherical alumina, avoiding the use of pore expanding agents and the introduction of impurity elements, and finally obtaining spherical alumina with the advantages of high strength and large pore volume.

[0008] The preparation method of spherical alumina of the present invention comprises the following steps:

[0009] Pseudo-boehmite powder is mixed with water to obtain a suspension, and then a peptizing agent is added for peptization to obtain an aluminum sol; a cross-linking substrate and a cross-linking agent are added to the aluminum sol to obtain a sol containing a prepolymer, and then a coagulant is added to obtain a mixed sol; the mixed sol is dripped into a hot oil column for molding, and spherical aluminum oxide is obtained after aging, washing, drying and calcining;

[0010] The cross-linking substrate is at least one of soluble starch, cellulose, alginate, polyvinyl amide, and polyvinyl alcohol; the cross-linking agent is at least one of aldehydes such as formaldehyde, chloroacetaldehyde, propionaldehyde, and butyraldehyde.

[0011] Preferably, the solid content of the suspension is 10 wt% to 30 wt%.

[0012] Preferably, the peptizing agent is at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution and citric acid solution.

[0013] Preferably, the concentration of the acid in the peptizing agent is 30 wt % to 70 wt %.

[0014] Preferably, the mass ratio of the peptizing agent to water is 1:(15-50).

[0015] Preferably, the mass ratio of the cross-linked substrate to the pseudo-boehmite powder is (0.1-1):1;

[0016] Preferably, the mass ratio of the cross-linking agent to the pseudo-boehmite powder is (0.1-1):1;

[0017] Preferably, the mass ratio of the cross-linking agent to the cross-linking substrate is (1.5-2.5):1.

[0018] Preferably, the drying temperature is 40° C. to 120° C., and the drying time is 6 to 24 hours.

[0019] Preferably, the calcination temperature is 600° C. to 1200° C., and the calcination time is 2 to 8 hours.

[0020] Compared with the prior art, the beneficial technical effects of the present invention are:

[0021] 1. The present invention adopts a hot oil column molding method to prepare spherical alumina, adds a cross-linking compound to the sol, and optimizes the pore structure through the network structure formed by the cross-linking compound, so that the spherical alumina has a higher pore volume and specific surface area;

[0022] 2. The cross-linked compound used in the present invention can optimize the microporous structure and connect the pores. Compared with the currently commonly used pore-enlarging agents, the pore structure is better and the strength is higher;

[0023] 3. The present invention does not introduce impurity elements during the preparation of spherical alumina, and the added cross-linking compound can be completely removed during the high-temperature roasting process. The preparation process is simple and does not require the addition of new equipment. The large-scale industrial production of spherical alumina carriers can be quickly realized on the existing molding device;

[0024] 4. The spherical alumina prepared by the present invention has a pore volume of 0.60 cm 3 / g or more, and can be used as a catalyst carrier for propane dehydrogenation reaction. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] The invention provides a method for preparing spherical alumina. By introducing a cross-linked structure into a slurry, the spherical alumina finally prepared has a larger pore volume, a stable pore structure and higher strength.

[0027] The preparation method of spherical alumina of the present invention specifically comprises the following steps:

[0028] S1, mixing deionized water and pseudo-boehmite powder to obtain a suspension, then adding a peptizing agent, and obtaining an aluminum sol after a peptization reaction;

[0029] S2, adding a crosslinking substrate and a crosslinking agent to the aluminum sol prepared in step S1, and mixing them evenly to obtain a sol containing a prepolymer;

[0030] S3, mixing the prepolymer-containing sol with the coagulant, and stirring thoroughly to obtain a mixed sol;

[0031] S4, dropping the mixed sol of step S3 into a hot oil column filled with vacuum pump oil to form a gel ball, and then immersing the gel ball in the vacuum pump oil for aging;

[0032] S5. Wash the aged balls with deionized water until no vacuum pump oil remains, and then dry and calcine to obtain spherical alumina.

[0033] The first step of the present invention is to prepare aluminum sol. In some specific embodiments of the present invention, the solid content of the suspension is 10wt% to 30wt%; the peptizing agent is at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution, and citric acid solution; the concentration of acid in the peptizing agent is 30wt% to 70wt%; the mass ratio of the peptizing agent to water is 1:(15 to 50). In some preferred embodiments of the present invention, the peptizing agent is nitric acid. The present invention successfully prepares pseudo-boehmite powder into aluminum sol with uniform performance by reasonably selecting the peptizing agent and its ratio, laying the foundation for subsequent cross-linking and the formation of pore structure.

[0034] The second step of the present invention is to prepare a sol containing a prepolymer. In some specific embodiments of the present invention, the cross-linked substrate is at least one of soluble starch, cellulose, alginate, polyvinyl amide, and polyvinyl alcohol; the mass ratio of the cross-linked substrate to the pseudo-boehmite powder is (0.1-1):1; the cross-linking agent is at least one of aldehydes such as formaldehyde, chloroacetaldehyde, propionaldehyde, butyraldehyde, etc.; the mass ratio of the cross-linking agent to the pseudo-boehmite powder is (0.1-1):1; the mass ratio of the cross-linking agent to the cross-linked substrate is (1.5-2.5):1. In some preferred embodiments of the present invention, the cross-linked substrate is soluble starch and / or polyvinyl amide; the cross-linking agent is formaldehyde and / or chloroacetaldehyde. The present invention forms a uniform system to be cross-linked by adding a cross-linked substrate, which provides a basis for the subsequent action of the cross-linking agent. The addition of the cross-linked substrate helps to produce uniformly connected large pores inside the alumina spheres and increase the pore volume of the material. The ratio of the cross-linked substrate to the pseudo-boehmite powder affects the pore volume and material strength, so the mass ratio of the cross-linked substrate to the pseudo-boehmite powder of the present invention is preferably (0.1-1):1.

[0035] The third step of the present invention is to prepare a mixed sol. In some specific embodiments of the present invention, the coagulant is a hexamethylenetetramine solution, and its mass fraction is 20% to 40%; the amount of the coagulant added is 20 to 60% of the mass of the sol containing the prepolymer. The present invention accelerates the gelation reaction by the coagulant, providing a basis for the subsequent formation of gel balls. Limiting the amount of the coagulant added can ensure the molding quality and internal structure uniformity of the gel balls.

[0036] The fourth step of the present invention is to prepare gel balls and perform aging treatment on them. In some specific embodiments of the present invention, the oil phase of the hot oil column is vacuum pump oil, the hot oil temperature is 80°C to 90°C; the aging temperature is 100°C to 140°C, and the aging time is 2 to 8h. In some preferred embodiments of the present invention, the hot oil temperature is 85°C; the aging temperature is 6h. The present invention drips the mixed sol into the hot oil column to form regular spherical gel particles through the surface tension of the droplets and the action of the coagulant. Immersing the gel balls in vacuum pump oil for aging helps to further strengthen the gel network structure and improve the mechanical strength and pore structure stability of the sphere. The aging process makes the chemical and physical properties inside and outside the gel balls tend to be consistent through cross-linking reactions and structural rearrangement.

[0037] The fifth step of the present invention is to prepare spherical alumina. In some specific embodiments of the present invention, the drying temperature is 40°C to 120°C, and the drying time is 6 to 24 hours; the calcination temperature is 600°C to 1200°C, and the calcination time is 2 to 8 hours. In some preferred embodiments of the present invention, the drying temperature is 100°C, and the drying time is 8 hours; the calcination temperature is 900°C, and the calcination time is 4 hours. The present invention removes the vacuum pump oil, coagulant and unreacted products remaining on the surface and inside of the gel ball by washing with deionized water, so as to avoid the influence of impurities on subsequent treatment and final product performance. The drying step is used to remove moisture from the sphere, ensure the stability of the ball structure and avoid cracks during calcination. The calcination step removes the organic matter remaining in the cross-linking agent and the cross-linking molecules, and at the same time strengthens the network structure of the spherical alumina by high temperature. During the high-temperature calcination process, the network structure formed by cross-linking is further converted into a stable interconnected channel to form a large pore volume structure. Calcination also improves the mechanical strength and thermal stability of the alumina sphere to meet the needs of practical applications.

[0038] In order to further illustrate the present invention, the following examples are provided for detailed description. The raw materials used in the following examples of the present invention are all commercially available.

[0039] Unless otherwise specified, all experiments were repeated 3 times and the results were expressed as mean values.

[0040] Example 1 A method for preparing spherical alumina, the steps are as follows:

[0041] S1. Take 15g of pseudo-boehmite powder and add it into 78g of deionized water to form a suspension. Slowly add 2g of nitric acid to the suspension and peptize for 1h to obtain aluminum sol.

[0042] S2, adding 2 g of soluble starch to the aluminum sol and stirring evenly, and then adding 3 g of formaldehyde to obtain a sol containing a prepolymer;

[0043] S3, mixing the prepolymer-containing sol with 40 g of a 40% hexamethylenetetramine solution, and stirring thoroughly to obtain a mixed sol;

[0044] S4, dropping the mixed sol into a hot oil column filled with vacuum pump oil, the hot oil temperature is 85°C, to obtain gel balls, and then immersing the gel balls in vacuum pump oil and aging at 140°C for 6h;

[0045] S5. Wash the pellets with deionized water, place them in an oven at 100°C to dry for 8 hours, transfer them to a muffle furnace, and calcine them at 900°C for 4 hours in an air atmosphere. After cooling to room temperature, spherical alumina is obtained.

[0046] Example 2 A method for preparing spherical alumina, the steps are as follows:

[0047] S1. Take 15g of pseudo-boehmite powder and add it into 78g of deionized water to form a suspension. Slowly add 2g of nitric acid to the suspension and peptize for 1h to obtain aluminum sol.

[0048] S2, adding 2 g of polyvinyl amide to the aluminum sol and stirring evenly, and then adding 3 g of formaldehyde to obtain a sol containing a prepolymer;

[0049] S3, mixing the prepolymer-containing sol with 40 g of a 40% hexamethylenetetramine solution, and stirring thoroughly to obtain a mixed sol;

[0050] S4, dropping the mixed sol into a hot oil column filled with vacuum pump oil, the hot oil temperature is 85°C, to obtain gel balls, and then immersing the gel balls in vacuum pump oil and aging at 140°C for 6h;

[0051] S5. Wash the pellets with deionized water, place them in an oven at 100°C to dry for 8 hours, transfer them to a muffle furnace, and calcine them at 900°C for 4 hours in an air atmosphere. After cooling to room temperature, spherical alumina is obtained.

[0052] Example 3 A method for preparing spherical alumina, the steps are as follows:

[0053] S1. Take 15g of pseudo-boehmite powder and add it into 78g of deionized water to form a suspension. Slowly add 2g of nitric acid to the suspension and peptize for 1h to obtain aluminum sol.

[0054] S2, adding 2 g of soluble starch to the aluminum sol and stirring evenly, and then adding 3 g of chloroacetaldehyde to obtain a sol containing a prepolymer;

[0055] S3, mixing the prepolymer-containing sol with 40 g of a 40% hexamethylenetetramine solution, and stirring thoroughly to obtain a mixed sol;

[0056] S4, dropping the mixed sol into a hot oil column filled with vacuum pump oil, the hot oil temperature is 85°C, to obtain gel balls, and then immersing the gel balls in vacuum pump oil and aging at 140°C for 6h;

[0057] S5. Wash the pellets with deionized water, place them in an oven at 100°C to dry for 8 hours, transfer them to a muffle furnace, and calcine them at 900°C for 4 hours in an air atmosphere. After cooling to room temperature, spherical alumina is obtained.

[0058] Example 4 A method for preparing spherical alumina, the steps are as follows:

[0059] S1. Take 15g of pseudo-boehmite powder and add it into 78g of deionized water to form a suspension. Slowly add 2g of nitric acid to the suspension and peptize for 1h to obtain aluminum sol.

[0060] S2, adding 2 g of soluble starch to the aluminum sol and stirring evenly, and then adding 3 g of formaldehyde to obtain a sol containing a prepolymer;

[0061] S3, mixing the prepolymer-containing sol with 40 g of a 40% hexamethylenetetramine solution, and stirring thoroughly to obtain a mixed sol;

[0062] S4, dropping the mixed sol into a hot oil column filled with vacuum pump oil to form a gel ball, the hot oil temperature is 85°C, and then immersing the gel ball in the vacuum pump oil and aging at 100°C for 6h;

[0063] S5. Wash the pellets with deionized water, place them in an oven at 100°C to dry for 8 hours, transfer them to a muffle furnace, and calcine them at 900°C for 4 hours in an air atmosphere. After cooling to room temperature, spherical alumina is obtained.

[0064] Comparative Example 1

[0065] S1. Take 15 g of pseudo-boehmite powder and add it into 78 g of deionized water to form a suspension. Slowly add 2 g of nitric acid to the suspension for peptization. After peptization for 1 hour, aluminum sol is obtained.

[0066] S2, adding 5 g of urea as a pore-enlarging agent to the aluminum sol, and stirring evenly to obtain a sol;

[0067] S3, mixing the sol obtained in S2 with 40 g of a 40% hexamethylenetetramine solution, and stirring thoroughly to obtain a mixed sol;

[0068] S4, dropping the mixed sol into a hot oil column filled with vacuum pump oil, the hot oil temperature is 85°C, to obtain gel balls, and then immersing the gel balls in vacuum pump oil and aging at 140°C for 6h;

[0069] S5. Wash the pellets with deionized water, place them in an oven at 100°C to dry for 8 hours, transfer them to a muffle furnace, and calcine them at 900°C for 4 hours in an air atmosphere. After cooling to room temperature, spherical alumina is obtained.

[0070] The performance of the alumina products obtained in the examples and comparative examples was tested, and the results are shown in Table 1.

[0071] Table 1 Alumina product performance test results

[0072] sample <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Pore ​​size (nm) Strength (N / grain) Example 1 135.3 0.65 18.7 53.2 Example 2 130.8 0.66 18.9 52.5 Example 3 128.4 0.64 17.5 54.6 Example 4 137.5 0.63 17.8 53.8 Comparative Example 1 123.2 0.48 18.3 23.3

[0073] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing spherical alumina, characterized in that: The following steps are involved: Pseudo-boehmite powder is mixed with water to obtain a suspension, and then a peptizing agent is added for peptization to obtain an aluminum sol; a cross-linking substrate and a cross-linking agent are added to the aluminum sol to obtain a sol containing a prepolymer, and then a coagulant is added to obtain a mixed sol; the mixed sol is dripped into a hot oil column for molding, and spherical aluminum oxide is obtained after aging, washing, drying and calcining; The cross-linking substrate is at least one of soluble starch, cellulose, alginate, polyvinyl amide, and polyvinyl alcohol; the cross-linking agent is at least one of aldehydes such as formaldehyde, chloroacetaldehyde, propionaldehyde, and butyraldehyde.

2. The preparation method according to claim 1, characterized in that: The solid content of the suspension is 10 wt% to 30 wt%.

3. The preparation method according to claim 1, characterized in that: The peptizing agent is at least one of hydrochloric acid solution, nitric acid solution, acetic acid solution and citric acid solution.

4. The preparation method according to claim 1, characterized in that: The mass concentration of the peptizing agent is 30% to 70%.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the peptizing agent to water is 1:(15-50).

6. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linked substrate to the pseudo-boehmite powder is (0.1-1):

1.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the pseudo-boehmite powder is (0.1-1):

1.

8. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the cross-linking substrate is (1.5-2.5):

1.

9. The preparation method according to claim 1, characterized in that: The drying temperature is 40° C. to 120° C., and the drying time is 6 to 24 hours.

10. The preparation method according to claim 1, characterized in that: The calcination temperature is 600° C. to 1200° C., and the calcination time is 2 to 8 hours.

Citation Information

Patent Citations

  • Method for manufacturing spheroidal alumina particles

    CN104039705A

  • Porous aluminum oxide ceramic and manufacturing method thereof

    CN110423135A

Cited By

  • Spherical alumina carrier for propane dehydrogenation and preparation method and catalyst thereof

    CN121869332A